Poročilo z 8. Svetovnega znanstvenega kongresa borilnih športov in borilnih veščin - IMACSSS - Šimenko, Jožef (Šport (Ljubljana), 2019)
This year the 8th World Scientific Congress of Combat Sports and Martial Arts was held between 10 and 12 October in Viseu, Portugal. It was co-organised by the Polytechnic Institute of Viseu - School of Education and Department of Sport Sciences, the International Martial Arts and Combat Sport Scientific Society (IMACSSS) as well as the Portuguese Network of Schools with Sport Studies in Polytechnic Public System Universities (REDESPP). The conference was organised under the auspices of the scientific and expert journals: Ido Movement for Culture - Journal of Martial Arts Anthropology, Research Journal of Budo and Revista de Artes Marciales Asiaticas (RAMA). All extended abstracts are available in the special edition of the last mentioned journal.
Keywords: borilne veščine; combat sports; conference; kongres; sport; šport